Factors influencing infant feeding practices of mothers and caregivers in the Polokwane Municipality - Limpopo Province - Makwela, Maishataba Solomon (My University, 2019)
Introduction: Exclusive breastfeeding for six months, with introduction of appropriate complimentary feeding at six months, continuing to 2 years and beyond comes highly recommended. Although breastfeeding rates have improved in South Africa, the prevalence still remains lower than the Rome target of 50%, supporting investigation into factors that influence infant feeding practices. Aim: The aim of this study was to describe infant feeding practices and to determine the factors influencing infant feeding practices of mothers and care givers of infants in the Polokwane Municipality - Limpopo Province. Methods: A cross-sectional health facility-based quantitative and descriptive survey was conducted using a validated-structured questionnaire. Interviews only were conducted to gather quantitative data. The questionnaires were administered to the mothers, one mother at a time. Chi–square tests were used to determine the relationship between selected variables, where p<0.05 was set as level of significance. Results: A total of 146 mothers participated in the study. All were biological mothers of infants. Ninety-four percent of the mothers initiated breastfeeding, however, at the time of data collection 8% of mothers had stopped. Of those who had stopped breastfeeding, 5% stopped earlier than one month after initiation. Thirty-nine percent of mothers breastfed exclusively, while 61% practiced mix feeding. A positive association between breast feeding practices and age of the mother (p<0.036) was observed. The reasons mothers reported for stopping breastfeeding were: mother was ill (45.4%) and going back to school or work (27.3%). Reasons for not breastfeeding were cited as: medical condition, not enough milk and infant refusal to breastfeed at 33.3%. Health workers are the main source of HIV information (77%). Mothers believe that HIV-positive women should breastfeed their infants (57%). Conclusion: breastfeeding initiation is well practiced. Exclusive breastfeeding during the first six months is rarely practiced. Infant formula and solid foods were introduced at an early age. Young mothers tend to stop exclusive breastfeeding compared to older mothers.
Thesis (MPH.) -- University of Limpopo, 2019
Keywords: Breastfeeding; Feeding practices; Breastfeeding -- South Africa -- Limpopo.; Bottle feeding -- South Africa -- Limpopo